2014
DOI: 10.15288/jsad.2014.75.704
|View full text |Cite
|
Sign up to set email alerts
|

Young Adult Drinking Partnerships: Alcohol-Related Consequences and Relationship Problems Six Years Later

Abstract: ABSTRACT. Objective: This study examines the association between young adult drinking partnerships (ages 18-26 years) and later alcohol-related problems and consequences, alcohol use, relationship quality, and relationship dissolution in adult relationships (ages 26-35). Method: Data came from the National Longitudinal Study of Adolescent Health (Add Health; Waves III and IV) with 1,347 young adults and their partners at Wave III, including dating, cohabiting, and married couples, and individual adult behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 33 publications
5
30
0
Order By: Relevance
“…Moreover, although the probability of getting married is the same as the general population, the probability of separation and divorce among couples where one person has an AUD is about four times higher (McCrady, 2012). Several studies have also identified discordance of drinking between partners as detrimental and a risk factor for separation and divorce (Homish & Leonard, 2007; Leonard, Smith, & Homish, 2014; Ostermann, Sloan, & Taylor, 2005; Torvik, Røysamb, Gustavson, Idstad, & Tambs, 2013; Wiersma & Fischer, 2014). …”
Section: Alcohol and The Marital Relationshipmentioning
confidence: 99%
“…Moreover, although the probability of getting married is the same as the general population, the probability of separation and divorce among couples where one person has an AUD is about four times higher (McCrady, 2012). Several studies have also identified discordance of drinking between partners as detrimental and a risk factor for separation and divorce (Homish & Leonard, 2007; Leonard, Smith, & Homish, 2014; Ostermann, Sloan, & Taylor, 2005; Torvik, Røysamb, Gustavson, Idstad, & Tambs, 2013; Wiersma & Fischer, 2014). …”
Section: Alcohol and The Marital Relationshipmentioning
confidence: 99%
“…Further, these earlier studies have found four (Wiersma et al, 2010; Wiersma & Fischer, 2014) or five (Roberts & Leonard, 1998; Wiersma et al, 2009) drinking classes. In contrast to earlier research, which has shown more dissimilarity in partner alcohol use/risk, we found more similarity in alcohol risk.…”
Section: Discussionmentioning
confidence: 86%
“…A second explanation may be that a socialization effect may occur in which dating partners in particular may drink similarly to their partner (e.g., Wiersma et al, 2011). This may reflect that drinking similarly makes dating couples feel more compatible (Wiersma & Fischer, 2014) and secure (Fischer & Wiersma, 2012). Relatedly, once partners have stronger levels of commitment in their partnership, they may feel less of a need to conform to their partners’ drinking (Fischer & Wiersma, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations